Using tech tools to decide where and what to restore - KS, Arpitha; Deepthi, R.; Bunyan, Milind (2024)
Diversity for Restoration (D4R) is a decision support tool, developed by The Alliance of Bioversity and CIAT, to assist in species selection for ecological restoration. Focused on southern India, the tool addresses the challenges of selecting suitable species by integrating climate change projections, site conditions, and community needs. Unlike traditional approaches, D4R uses habitat modelling and a trait-based scoring system to recommend species that align with restoration goals and environmental conditions. The D4R tool offers tree species after matching species to the best fit of the site conditions and restoration objectives. With a species pool of 250 native and exotic species, D4R offers a holistic solution for more effective and sustainable restoration projects.